Transformative Group Guidance Approaches: The Effectiveness of 'Tic Tac Toe' Simulation Game to Enhance Self-Harm Behavior Understanding - Safitri, Muetia Fadilah (Proceedings Series of Educational Studies, 2024)
American Psychiatric Association. (1998). Diagnostic and Statistical Manual of Mental Disorders. In Encyclopedia of Applied Psychology, Three-Volume Set. American Psychiatric Publishing. https://doi.org/10.1016/B0-12-657410-3/00457-8 Azizah, N., & Yasin, A. A. (2022). Efektifitas Pendekatan Konseling Behavioral Pada Perilaku Self Harm Di Manu Putri Buntet Pesantren. JIECO: Journal of Islamic Education Counseling, 2(1), 1–7. https://www.jurnal.stit-buntetpesantren.ac.id/index.php/jieco/article/view/120 Bariyyah, K., & Latifah, L. (2019). Kecerdasan Emosi Siswa Ditinjau dari Jenis Kelamin dan Jenjang Kelas. JPGI (Jurnal Penelitian Guru Indonesia), 4(2), 68. https://doi.org/10.29210/02379jpgi0005 Bariyyah, K., Riza, J. K., & Pambudi, P. R. (2019). Value Clarification Technique in Enhancing Forgiveness. Abjadia : International Journal of Education, 4(1), 1–11. https://doi.org/10.18860/abj.v4i1.6288 Batubara, J. R. (2016). Adolescent Development (Perkembangan Remaja). Sari Pediatri, 12(1), 21. https://doi.org/10.14238/sp12.1.2010.21-9 Cella, S., Cipriano, A., Aprea, C., Milano, W., Carizzone, F., & Cotrufo, P. (2022). Non-suicidal self-injury in eating disorders: Prevalence, characteristics, DSM-5 proposed diagnostic criteria, and correlates. Journal of Af ective Disorders Reports, 7, 100292. https://doi.org/10.1016/j.jadr.2021.100292 Diananda, A. (2019). Psikologi Remaja Dan Permasalahannya. Journal ISTIGHNA, 1(1), 116–133. https://doi.org/10.33853/istighna.v1i1.20 Favril, L., Yu, R., Hawton, K., & Fazel, S. (2020). Risk factors for self-harm in prison: a systematic review and meta-analysis. The Lancet Psychiatry, 7(8), 682–691. https://doi.org/10.1016/S2215-0366(20)30190-5 Fitzgerald, J., & Curtis, C. (2017). Non-suicidal self-injury in a New Zealand student population: Demographic and self-harm characteristics. New Zealand Journal of Psychology, 46(3), 156–163. Gillies, D., Christou, M., Dixon, A., Featherston, O., Rapti, I., Garcia, A. A., M, V.-K., Reebye, P., Christou, E., Al Kabir, N., & PA, C. (2018). Prevalence and Characteristics of Self-Harm in Adolescents: Meta-Analyses of Community-Based Studies 1990-2015. J Am Acad Child Adolesc Psychiatry, 57(10), 733–741. https://doi.org/10.1016/j.jaac.2018.06.018 Hajek Gross, C., Oehlke, S. M., Prillinger, K., Goreis, A., Plener, P. L., & Kothgassner, O. D. (2024). Efficacy of mentalization-based therapy in treating self-harm: A systematic review and meta-analysis. Suicide and Life-Threatening Behavior, 54(2), 317–337. https://doi.org/10.1111/sltb.13044 Hartanti, J. (2022). Bimbingan Kelompok. UD Duta Sablon. Insani, M. S., & Savira, S. I. (2023). Studi Kasus : Faktor Penyebab Perilaku Self-Harm Pada Remaja Perempuan Case Study: Causative Factor Self-Harm Behavior in Adolescent Female. Character : Jurnal Penelitian Psikologi, 10(2), 439–454. Iob, E., Steptoe, A., & Fancourt, D. (2020). Abuse, self-harm and suicidal ideation in the UK during the COVID-19 pandemic. British Journal of Psychiatry, 217(4), 543–546. https://doi.org/10.1192/bjp.2020.130 Istiana, D., Safitri, R. P., Pratiwi, E. A., & Oksafitri, A. (2023). Hubungan Loneliness dengan Perilaku SelfHarm pada Remaja. Jurnal Ilmu Kesehatan Dharmas Indonesia, 3(2), 57–62. https://doi.org/10.56667/jikdi.v3i2.1213 Katrina G, W., Sarah E, H., Gowri, R., Philip, H., Tatiana L, T. S., Ellen, T., & Keith, H. (2021). Interventions for self-harm in children and adolescents. Cochrane Database of Systematic Reviews, 2021(3). https://doi.org/10.1002/14651858.CD013667.pub2 Knipe, D., Padmanathan, P., Newton-Howes, G., Chan, L. F., & Kapur, N. (2022). Suicide and self-harm. The Lancet, 399(10338), 1903–1916. https://doi.org/10.1016/S0140-6736(22)00173-8 Miller, M., Redley, M., & Wilkinson, P. O. (2021). A qualitative study of understanding reasons for selfharm in adolescent girls. International Journal of Environmental Research and Public Health, 18(7). https://doi.org/10.3390/ijerph18073361 Nawaz, R. F., Anderson, J. K., Colville, L., Fraser-Andrews, C., & Ford, T. J. (2024). Review: Interventions to prevent or manage self-harm among students in educational settings – a systematic review. Child and Adolescent Mental Health, 29(1), 56–69. https://doi.org/10.1111/camh.12634 Novianti, B., Bariyyah, K., & Permatasari, D. (2019). Pengaruh Experiental Learning Terhadap Interaksi Sosial Siswa. Prosiding Seminar Nasional Pendidikan Dan Pembelajaran Bagi Guru Dan Dosen, 3(2017), 413–417. Patchin, J. W., Hinduja, S., & Meldrum, R. C. (2023). Digital self-harm and suicidality among adolescents. Child and Adolescent Mental Health, 28(1), 52–59. https://doi.org/10.1111/camh.12574 Putri, T. H., & Dewi, V. (2023). Gambaran Perilaku Non-Suicidal Self Injury (NSSI) Pada Remaja di Masa Pandemi: Literature Review. Jurnal Keperawatan Jiwa (JKJ) : Persatuan Perawat Nasional Indonesia, 11(2), 415–428. Reichl, C., & Kaess, M. (2021). Self-harm in the context of borderline personality disorder. Current Opinion in Psychology, 37, 139–144. https://doi.org/10.1016/j.copsyc.2020.12.007 Riza, Anwar, K., & Aminah. (2019). Studi Layanan Bimbingan dan Konseling yang Dapat Mengatasi Perilaku Self Injury Pada Siswa Kelas 8 di SMP N 13 Banjarmasin. Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 5(3), 1–5. Santrock, J. W. (2014). Adolescence (Fifteenth edition). McGraw-Hill Education. Tarigan, T., & Apsari, N. C. (2021). Perilaku Self-Harm Atau Melukai Diri Sendiri Yang Dilakukan Oleh Remaja (Self-Harm or Self-Injuring Behavior By Adolescents). Focus : Jurnal Pekerjaan Sosial, 4(2), 213–224. https://doi.org/10.24198/focus.v4i2.31405 Whitlock, J. (2009). The Cutting Edge: Non-Suicidal Self-Injury in Adolescence. Article of psychology. Wong, B. H. C., Cross, S., Zavaleta-Ramírez, P., Bauda, I., Hoffman, P., Ibeziako, P., Nussbaum, L., Berger, G. E., Hassanian-Moghaddam, H., Kapornai, K., Mehdi, T., Tolmac, J., Barrett, E., Romaniuk, L., Davico, C., Moghraby, O. S., Ostrauskaite, G., Chakrabarti, S., Carucci, S., … Ougrin, D. (2023). Self-Harm in Children and Adolescents Who Presented at Emergency Units During the COVID-19 Pandemic: An International Retrospective Cohort Study. Journal of the American Academy of Child and Adolescent Psychiatry, 62(9), 998–1009. https://doi.org/10.1016/j.jaac.2022.11.016 Yohardini, G., Bariyyah, K., & Susanti, R. H. (2017). Efektifitas Bimbingan Kelompok dengan Teknik Simulasi Untuk Meningkatkan Kemampuan Komunikasi Interpersonal Siswa Kelas X SMA Al Rifa’ie Gondanglegi. Jurnal Konseling Indonesia, 2(2), 49–56. https://ejournal.unikama.ac.id/index.php/JKI/article/view/1936/1540 Yuliana, Sinring, A., & Juwarningsih. (2023). Cognitive Behavior Therapy dengan Teknik Rekonstruksi Kogntif Untuk Mengurangi Perilaku Self-Harm Peserta Didik Di SMAN 2 Tarakan. Jurnal Pemikiran Dan Pengembangan Pembelajaran, 5(3), 229–234. https://ejournal-jp3.com/index.php/Pendidikan/article/view/935